Kontribusi Objek Wisata Terhadap Pendapatan Masyarakat di Kabupaten Tulang Bawang Barat di Era Society 5.0 - Putri, Fani Monada; Himawati, Ratna (Musyarakah: Journal of Sharia Economic (MJSE), 2023)
The tourism sector is a booster for economic growth in a country. According to the Travel and Tourism Competitiveness Index (TTCI) ranking published by the World Economic Forum (WEF), Indonesia is ranked 40th (out of 140 countries) in 2019 with an increasing trend. This indicates that there is a huge potential in Indonesia. Lampung is also known as a tourist destination, one of the relatively new districts with several tourist destinations, one of which is the Islamic Center This study aims to determine the contribution of tourist attractions to the income of people in West Tulang Bawang in the Era of Society 5.0. The era of Society 5.0 is a digital era in which the basic component is humans utilizing technology. Tourist attractions greatly contribute to the income of the surrounding community, especially the people of West Tulang Bawang Barat.